ANALYSIS OF THE ANXIETY ABOUT COVID-19 PANDEMIC WITH BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS - Febriyanti, Ni Made Ari; Dewi, A.A Santi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: The postpartum period is a process that begins after the birth of the baby until the organs return to the way they were before pregnancy. There are complex physical and psychological changes. One of the psychological disorders that often occurs after childbirth is anxiety. This anxiety disorder will also indirectly affect the release of breast milk so that it interferes with the process of breastfeeding. The purpose of this study was to determine the relationship between anxiety during the COVID-19 pandemic and the production of breast milk in breastfeeding mothers. Methods: The design of this study was cross-sectional analytic. This study was carried out at East Denpasar Health Center I with a sample size of 30 respondents who met the inclusion criteria. The sampling technique of this research is purposive sampling. The independent variable in this study is anxiety and the dependent variable is the breast milk production. Data were collected using the Zung Self Rating Anxiety Scale (ZSAS) questionnaire and data analysis was carried out in stages including univariate and bivariate (Rank Spearman). Result: The results showed that most (60%) of respondents did not experience anxiety and most (60%) of respondents released breast milk quickly. Bivariate results show that there is a significant relationship between anxiety during the COVID-19 pandemic and the production of breast milk in breastfeeding mothers (p = 0.0001) with a correlation coefficient of 0.738. Conclusion: There is a relationship between anxiety and breastmilk production. The lower mother's anxiety, the better the production of her milk.